2006
DOI: 10.1128/iai.00843-06
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Hemozoin by Monocytes Down-Regulates Interleukin-12 p40 (IL-12p40) Transcripts and Circulating IL-12p70 through an IL-10-Dependent Mechanism: In Vivo and In Vitro Findings in Severe Malarial Anemia

Abstract: Severe malarial anemia (SMA) is a primary cause of morbidity and mortality in immune-naïve infants and young children residing in areas of holoendemic Plasmodium falciparum transmission. Although the immunopathogenesis of SMA is largely undefined, we have previously shown that systemic interleukin-12 (IL-12) production is suppressed during childhood blood-stage malaria. Since IL-10 and tumor necrosis factor alpha (TNF-␣) are known to decrease IL-12 synthesis in a number of infectious diseases, altered transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 50 publications
12
75
2
Order By: Relevance
“…Although IL-23 and IL-12 share the p40 subunit [17], levels of IL-23 were elevated in children with malarial anemia, while plasma IL-12 concentrations progressively declined with increasing anemia severity. The decrease in IL-12 with increasing disease severity parallels previous findings in African children residing in areas with intense malaria transmission [12][13][14]29,[43][44][45]. In addition, examination of the IL-12 to IL-23 ratio revealed that SMA is characterized by low levels of IL-12 relative to IL-23.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Although IL-23 and IL-12 share the p40 subunit [17], levels of IL-23 were elevated in children with malarial anemia, while plasma IL-12 concentrations progressively declined with increasing anemia severity. The decrease in IL-12 with increasing disease severity parallels previous findings in African children residing in areas with intense malaria transmission [12][13][14]29,[43][44][45]. In addition, examination of the IL-12 to IL-23 ratio revealed that SMA is characterized by low levels of IL-12 relative to IL-23.…”
Section: Discussionsupporting
confidence: 82%
“…Results presented here showing that the relative expression of IL-10 to IL-23 progressively increased with increasing anemia severity may suggest that IL-10 could have a suppressive effect on IL-23 production. Our previous investigations illustrate that phagocytosis of malarial pigment by monocytes causes enhanced production of IL-10 that, in turn, suppresses IL-12 [29]. These results have important implications in the pathogenesis of malarial anemia since IL-12 is required for promotion of erythropoiesis through its ability to enhance erythroid burst (BFU-E) and colony forming units (CFU-E) [47,48].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations